TINDAKAN REVIEW MENGGUNAKAN POTONGAN KARYA SINEMATOGRAFI TANPA IZIN MELALUI APLIKASI TIKTOK - Thereza Hilya Hutasoit (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
Piracy of cinematographic works is becoming more and more common in various internet media. In the Tiktok application, the act of piracy that occurs is the upload of movie clips into several parts, without including the source and permission of the owner of the film. The purpose of this study is to find out how the legal protection of copyright owners on cinematographic works in the Tiktok application and to find out whether an upload action in the form of a film review that uses cinematographic pieces through Tiktok social media is included in the act of piracy. The research method in this paper is normative juridical with a conceptual and normative problem approach. This study finds that the protection of the rights to the creation of cinematographic works on Tiktok social media in the form of preventive and repressive measures has been pursued by the government through the regulation of Law No. 28 of 2014 concerning copyright. The TikTok application has also attempted to provide legal protection for copyright holders with a clause contained in Tiktok's Terms of Service and Community Guidelines which prohibits uploading content that violates the copyright. Review action is one form of marketing known as E-WOM which is considered effective in attracting consumer interest in goods or services so that it can benefit the holder of the economic rights of a creator but based on article 133 section 4 review actions that include pieces of cinematographic works are not justified because they meet elements of piracy. Keywords : copyright, Film Review, TikTok